2000
DOI: 10.1590/s0004-282x2000000100007
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging in the evaluation of patients with aseptic meningoencephalitis and connective tissue disorders

Abstract: -Objective: To describe the role of magnetic resonance imaging (MRI) in the evaluation of patients with chronic and recurrent aseptic meningitis.Method: A retrospective study of five patients with aseptic meningoencefalitis diagnosed by clinical and CSF findings. CT scans showed without no relevant findings. Results: MRI showed small multifocal lesions hyperintense on T2 weighted images and FLAIR, with mild or no gadolinium enhancement, mainly in periventricular and subcortical regions. Meningoencephalitis pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 8 publications
(16 reference statements)
1
6
1
Order By: Relevance
“…Similarly, other groups have reported that small cortical or subcortical lesions hyperintense in T2 weighting are consistent with small vessel vasculitis and that gadolinium enhancement in T1 weighting in subarachnoid spaces suggests systemic disease rather than idiopathic meningitis. 14,15 Despite a tendency for a higher protein level in CSF to be associated with SID, we did not find any significant differences in the CSF analysis between idiopathic and SIDrelated meningitis. Some patients with idiopathic meningitis and no clear-cut SID appear to have 'borderline' characteristics, including the presence of extraneurological signs with abnormal MRI findings, with some patients requiring steroid therapy.…”
contrasting
confidence: 76%
“…Similarly, other groups have reported that small cortical or subcortical lesions hyperintense in T2 weighting are consistent with small vessel vasculitis and that gadolinium enhancement in T1 weighting in subarachnoid spaces suggests systemic disease rather than idiopathic meningitis. 14,15 Despite a tendency for a higher protein level in CSF to be associated with SID, we did not find any significant differences in the CSF analysis between idiopathic and SIDrelated meningitis. Some patients with idiopathic meningitis and no clear-cut SID appear to have 'borderline' characteristics, including the presence of extraneurological signs with abnormal MRI findings, with some patients requiring steroid therapy.…”
contrasting
confidence: 76%
“…Based on his neurological presentation, his ear lobe biopsy finding, brain MRI findings [ 3 ], and negative serologies, he was given a diagnosis of RP with meningoencephalitis.…”
Section: Case Reportmentioning
confidence: 99%
“…MRI findings of small cortical and subcortical multifocal lesions hypointense in T1 weighted and hyperintense in T2 with mild or no gadolinium enhancement suggestive of small vessel vasculitis, mainly in periventricular and subcortical regions, is suggestive of chronic or recurrent AM (Appenzeller et al, 2000).…”
Section: Neuroimaging Studies In Patients With Iihmentioning
confidence: 99%